Lesson Study-Based Learning of English Teachers' Pedagogic Competence - Rizkariani Sulaiman; Umar Mansyur; Sulastri Sulastri (Jurnal Sinestesia, 2022)
Pedagogic competence is one of the four competencies that needs to be developed on an ongoing basis by a teacher, especially in educational developments that demand strengthening the profile of Pancasila learners who are able to think critically and have character. To deal with this, the demands of 21st century teacher competence can be handled through Lesson Study (LS). LS is teacher development assistance which is considered quite effective as a forum for collaboration between fellow study teachers to develop learning tools with the stages of plan, do and see. The purpose of this research is to find out how Lesson Study implementation of the pedagogic competence of English teachers at SMPN 23 Makassar. This study used descriptive qualitative method. The research was carried out at UPT SPF SMPN 23 Makassar in semester I (one) of the 2022/2023 academic year. Before the research was carried out, researchers and teachers discussed in advance about the process of implementing learning with the Lesson Study platform, the timeline of activities and agreed subject matter topics. The research subject was English teachers at SMPN 23 Makassar who acted as model teacher. The research instrument used was in the form of teacher observation sheets, namely: English teacher pedagogical competency observation sheets and observation sheets for the implementation of Lesson Study. The teacher's pedagogical competence increased from good to very good criteria after going through the Lesson Study stages, especially in the aspects of mastering student characteristics, mastery of learning theories and principles, and communication/interaction in class. In order for the teacher's pedagogical competence to remain of high quality and controlled, the Lesson Study for Learning Community needs to be organized by the school leadership as a forum for continuing teacher competency development.